2016
DOI: 10.1080/10715762.2016.1252839
|View full text |Cite
|
Sign up to set email alerts
|

Plant sterol-enriched soy milk consumption modulates 5-lipoxygenase, 12-lipoxygenase, and myeloperoxidase activities in healthy adults – a randomized-controlled trial

Abstract: A randomized, double blind, placebo-controlled and crossover study was conducted to simultaneously measure the effects, after 3-h and 4-week daily exposure to plant sterols-enriched food product, on inflammation, oxidative status, 5-lipoxygenase, 12-lipoxygenase, and myeloperoxidase activities in healthy adults. Eighteen healthy participants (67% female, 35.3 (mean) ± 9.5 (SD) years, mean body mass index 22.8 kg m) received two soy milk (20g) treatments daily: placebo and one containing 2.0 g free plant sterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…These results suggest a relationship between phytosterols and activation of anti-inflammatory response. Another study including 18 healthy participants (85) undergoing a milk supplemented with plant sterols intervention (2.0 g free phytosterols) during 4 weeks found results following a similar trend. Hs-CRP serum levels significantly diminished after the intervention −0.32 mg/L ( P < 0.05), and plasma lipoxin A4 (LXA 4 ) concentrations increased (0.12 nmol/L, P < 0.05) as did nitrite and nitrate levels ( P < 0.05, both).…”
Section: Phytosterolsmentioning
confidence: 70%
“…These results suggest a relationship between phytosterols and activation of anti-inflammatory response. Another study including 18 healthy participants (85) undergoing a milk supplemented with plant sterols intervention (2.0 g free phytosterols) during 4 weeks found results following a similar trend. Hs-CRP serum levels significantly diminished after the intervention −0.32 mg/L ( P < 0.05), and plasma lipoxin A4 (LXA 4 ) concentrations increased (0.12 nmol/L, P < 0.05) as did nitrite and nitrate levels ( P < 0.05, both).…”
Section: Phytosterolsmentioning
confidence: 70%
“…Six studies were conducted in women (Hsu, Kuo, & Huang, ; Li & Xing, ; Matvienko et al, ; Plat & Mensink, ; Plat, Van Onselen, Van Heugten, & Mensink, ; Stelmach‐Mardas, Walkowiak, Zagrodzki, Grygiel‐Górniak, & Przysławski, ), five in men (Esther et al, ; Gao, Wang, Wang, & Guo, ; Jones, Ntanios, Raeini‐Sarjaz, & Vanstone, ; Plat et al, ), and the rest of eligible studies involved both genders. Forty‐seven studies had a single‐arm parallel group whereas 32 studies had a crossover design (Abumweis et al, ; de Graaf et al, ; De Smet et al, ; Demonty, Chan, Pelled, & Jones, ; Esther et al, ; Farquhar & Sokolow, ; Fuentes et al, ; Hallikainen et al, ; Hendriks, Weststrate, Van Vliet, & Meijer, ; Ho, Liu, & Loke, ; Jones, Vanstone, Raeini‐Sarjaz, & St‐Onge, ; Kassis, Vanstone, Abumweis, & Jones, ; Naumann, Plat, & Mensink, ; Neil, Meijer, & Roe, ; Ottestad et al, ; Plat et al, ; Plat & Mensink, ; Theuwissen & Mensink, ; Thomsen, Hansen, Christiansen, Green, & Berger, ; Volpe et al, ). Included studies were carried out in patient with dyslipidemia (Varady et al, ; Ottestad et al, ; Gylling, Hallikainen, Nissinen, & Miettinen, ; Bañuls et al, ; Hironaka, Shioya, Matsubara, Matsuoka, & Itakura, ; Sukmaniah et al, ; Becker et al, ; Stelmach‐Mardas et al, ; Furuncuoğlu, Başar, Alici, & Şengül, ; Abumweis et al, ; Cabezas, De Vries, Van Oostrom, Iestra, & Van Staveren, ; de Graaf et al, 2002; De Jong et al, ; Demonty et al, ; Fuentes et al, ; Gylling et al, ; Hallikainen, Kurl, Laakso, Miettinen, & Gylling, ; Hallikainen, Sarkkinen, Gylling, Erkkilä, & Uusitupa, ; Hallikainen & Uusitupa, ; Hendriks et al, ; Hsu et al, ; Jones et al, ; Jones et al, …”
Section: Resultsmentioning
confidence: 99%
“…Forty‐seven studies had a single‐arm parallel group whereas 32 studies had a crossover design (Abumweis et al, ; de Graaf et al, ; De Smet et al, ; Demonty, Chan, Pelled, & Jones, ; Esther et al, ; Farquhar & Sokolow, ; Fuentes et al, ; Hallikainen et al, ; Hendriks, Weststrate, Van Vliet, & Meijer, ; Ho, Liu, & Loke, ; Jones, Vanstone, Raeini‐Sarjaz, & St‐Onge, ; Kassis, Vanstone, Abumweis, & Jones, ; Naumann, Plat, & Mensink, ; Neil, Meijer, & Roe, ; Ottestad et al, ; Plat et al, ; Plat & Mensink, ; Theuwissen & Mensink, ; Thomsen, Hansen, Christiansen, Green, & Berger, ; Volpe et al, ). Included studies were carried out in patient with dyslipidemia (Varady et al, ; Ottestad et al, ; Gylling, Hallikainen, Nissinen, & Miettinen, ; Bañuls et al, ; Hironaka, Shioya, Matsubara, Matsuoka, & Itakura, ; Sukmaniah et al, ; Becker et al, ; Stelmach‐Mardas et al, ; Furuncuoğlu, Başar, Alici, & Şengül, ; Abumweis et al, ; Cabezas, De Vries, Van Oostrom, Iestra, & Van Staveren, ; de Graaf et al, 2002; De Jong et al, ; Demonty et al, ; Fuentes et al, ; Gylling et al, ; Hallikainen, Kurl, Laakso, Miettinen, & Gylling, ; Hallikainen, Sarkkinen, Gylling, Erkkilä, & Uusitupa, ; Hallikainen & Uusitupa, ; Hendriks et al, ; Hsu et al, ; Jones et al, ; Jones et al, ; Kassis et al, ; Korpela et al, ; Lestiani et al, ; Matvienko et al, ; Neil et al, ; Plat & Mensink, ; Plat et al, ; Smet, Mensink, & Plat, ; Solà et al, ; Theuwissen and Mensink, 2007; Thomsen et al, ; Volpe et al, ; Woodgate, Chan, & Conquer, ), diabetes (Gao et al, …”
Section: Resultsmentioning
confidence: 99%
“…A recent randomised, double blind control trial using soy milk supplemented with 2g phytosterol (sitosterol, stigmasterol and campesterol) or placebo found that after 4 weeks of a daily regime, plasma and urine inflammatory markers such as leukotriene B4 and F2 isoprostanes, C-Reactive Protein (CRP) and lipid peroxidase activity were significantly reduced [43]. Serum CRP is used clinically as an inflammatory marker, and may be associated with an increased risk of some cancers, in particular, BCa [44].…”
Section: Phytosterol Intake and Cancer Incidencementioning
confidence: 99%